Comparative evaluation of pull-out bond strength of fiber post using different luting cements in endodontically treated teeth: An in-vitro study - Neha Singh; Ashima Garg; Rakesh Mittal (Wolters Kluwer Medknow Publications, 2021)
Aim: This study was aimed to evaluate and compare the pull-out bond strength of fiber post using glass ionomer cement (GIC), resin-modified glass ionomer cements (RMGIC), self-etch adhesive resin cement, and self-adhesive resin cement in endodontically treated teeth. Materials and Methods: Forty single-rooted teeth with single canal were decoronated, endodontically treated, post space were prepared and divided into four groups (n = 10) based on the cement used for luting the fiber post. Group 1: GIC, Group 2: RMGIC, Group 3: Self etch adhesive resin cement, Group 4: Self-adhesive resin cement. Pull-out test was evaluated for the prepared samples. Statistical analysis was performed using analysis of variance and Tukey's test (P = 0.05). Results: The mean pull-out bond strength of Group 4 was statistically higher than Group 1,2 and 3. Group 1 showed the least bond strength among all the groups. Conclusion: Within the limitation of this study, self-adhesive resin cements provide better bond strength of fiber post to root canal compared to self-etch adhesive resin cement and glass ionomer based cements.